THE EFFECT OF COMIC STRIPS TECHNIQUE AND LEARNING MOTIVATION TOWARD THE STUDENTS’ ACHIEVEMENT IN ENGLISH WRITING IN NURSING STUDENTS OF STIKES BULELENG - Marleni, Kadek Devi (Institut Hindu Dharma Negeri Denpasar, 2018)
This study aimed at investigating whether the implementation of comic stripstechnique and the students’ learning motivation gave a significant effect to the students’writing competency. The study was an experimental study by applying 2 x 2 factorialdesign. The population was 100 students of nursing programme which 2 classes were usedas the samples which were assigned into two groups, i.e. experimental group and controlgroup, byCluster Random Sampling. The research data were collected through tests that wereanalysed by usingStatistical Two-Way AnovaandTukey Test. The result shows that, first, therewas a significant difference on the students’ writing competency between the students whowere taught by using comic strips technique and conventional writing technique, in whichthe students who were taught by using comic strips technique had higher writingcompetency than those students who were taught by using conventional technique. Second,there was a significant interactional effect on the students’ writing competency between thetechnique applied and the students’ learning motivation. Third, there was a significantdifference on the students’ writing competency between the students who had high learningmotivation when they were taught by using comic strips technique and those who weretaught by using conventional technique, in which the students who had high learningmotivation taught by using comic strips technique had higher writing competency thanthose students who were taught by using conventional writing technique. Fourth, there wasa significant difference between the students’ writing competency of the students who hadlow learning motivation when they were taught by using comic strips technique and theywere taught by using conventional technique, in which the students who had low learningmotivation taught by using comic strip technique had higher writing competency than thosestudents who were taught by using conventional writing technique.